A Late presentation of Gossypiboma presenting as a cutaneous fistula with purulent discharge in an operated case of Lower segment caesarean section - Ojas Vijayanand Potdar; Akash Shah; Darshan Rathi; Prakhar Chaudhary; Ashish Chaubey (National Board of Examinations Journal of Medical Sciences, 2024)
Gossypiboma, a retained surgical sponge, is a rare complication following any surgical procedure and is primarily a result of human error. Such patients often have vague clinical presentations and the diagnosis often comes as a surprise and has serious medicolegal implications. We present a case of a 28-year-old female with a long-standing duration of 9 months with purulent discharge from the operated scar site of Lower segment caesarean section done 2 years back and then diagnosed to have a gossypiboma in the ureterovesical space causing structuring of the ipsilateral ureter which was successfully managed by Exploratory laparotomy with removal of the retained gossypiboma and right sided ureteric reimplantation.